Potential industrial utilization of pre-treated municipal solid waste incineration fly ash. Issue 7 (July 2018) - Yakubu, Yahaya; Zhou, Jun; Shu, Zhu; Tan, Yigen; Zhao, Zhengliang; Mbululo, Yassin
This study sought to establish the effectiveness of water washing pre-treatment on the quality of municipal solid waste incineration (MSWI) fly ash (FA) for reuse and solidification or stabilization (S/S). Initial analysis of the FA sample shows that it did not meet the USEPA-1311 toxicity characteristic leaching procedure (TCLP) regulatory limits of 2011. As a result, a two-stage water washing process was carried out an attempt to improve the quality of the MSWI FA. After the washing pre-treatment, the heavy metals in the FA sample met the regulatory limits, thereby making it non-toxic for reuse or safe disposal. The leachate from the washing process also passed regulatory standards of China (GB 8978 – 1996) and the 2011 USEPA-1311. The washing process successfully removed more than 98% of each heavy metal under study. The process was excellent at removing cadmium (99.99%) and very good at removing the rest of the heavy metals. The 28-day compressive strength increased as the quantity of FA decreased. Also, all the heavy metals in the samples prepared with the pre-treated FA met the USEPA-1311 TCLP regulatory limit for reuse and safe disposal. The heavy metals leachability and compressive strength tests showed that the effect of cement-based S/S was largely influenced by its quantity in the samples. The highest compressive strength was attained by using 55% of the FA as replacement for cement. However, FA replacements of up 70% also yielded good results that met the 1989 USEPA standard of 0.34 MPa (50 psi).